The Wiley-Blackwell encyclopedia of globalization - Ritzer, George (Wiley-Blackwell encyclopedias in social science, 2012)
Containing over 600 entries, this five-volume set is the definitive reference work on globalization for students, researchers, and academics on this topic. Edited by one of the leading authorities in the field, the work brings together specially commissioned entries from the world's best scholars and teachers